PERAN GREEN MARKETING DALAM MENINGKATKAN CITRA LENGKUNG LANGIT SEBAGAI ECO-TOURISM - Jernic Tantty Amoy; Naila Davina Keysa; Reva Marya; Septia Wulanda; Yoga Andika; Ayu Nursari (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Increasing awareness of environmental sustainability has encouraged the growth of eco-tourism as an important segment of the tourism industry. This study aims to examine the role of green marketing in enhancing the image of Lengkung Langit as an eco-tourism destination and to analyze its influence on visitors' perceptions and the destination's reputation. Green marketing in this study consists of four dimensions: environmental communication, evidence of sustainable practices, environmental certification, and local community involvement. Meanwhile, the image of an eco-tourism destination is measured through three dimensions: environmental perception, social reputation, and information credibility. This study employs a quantitative approach using a survey of 250–350 visitors to Lengkung Langit, selected through purposive sampling. Data are analyzed using multiple linear regression and hypothesis testing to empirically examine the relationships among variables. The findings are expected to demonstrate that green marketing has a positive and significant effect on the image of Lengkung Langit as an eco-tourism destination. These findings are anticipated to provide practical recommendations for destination managers in strengthening sustainable green marketing strategies. Furthermore, this study is expected to enrich the academic literature on the relationship between green marketing and the image of sustainable tourism destinations in Indonesia